Principles of forensic medicine including toxicology - Nandy, Apurba (New Central Book Agency, 2010)
This authentic book in the field of Forensic Medicine is intended for undergraduate medical students and post graduate students of Forensic Medicine. It will also serve as a good reference book for medical practitioners lawyers and those engaged in the crucial investigation of criminal cases. Being an extremely well-written book it has incorporated the medico-legal aspects of certain current issues and has also rectified some of the fallacies about the applicability of this branch of science in the practical field.